2019
DOI: 10.5539/ijef.v11n10p140
|View full text |Cite
|
Sign up to set email alerts
|

FDI and Infrastructure Improvement of ASEAN

Abstract: As a synthesis of capital, technology, knowledge and information, foreign direct investment(FDI) has a significant impact on the host country's economy, and the infrastructure is no exception which is an important part of one country's economy. This paper aims to empirically analyse the impact of FDI on infrastructure, using the panel data of ASEAN countries’ infrastructure and FDI from 2003 to 2017 and compare the infrastructure effect of FDI from China and FDI from countries besides China. Result shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Literature on FDI and Infrastructure Nourzad, Greenwold, and Yang (2014) concluded that economic growth and infrastructure attract FDI. The study explored the relationship between foreign direct investment and infrastructure construction and confirmed that FDI improves infrastructure development; Sui, Huang, and Huang (2017) and Huang, Liu, Cai, Hao, and Lei (2018) for China, Chakrabarti et al (2017) for India and Jiang, Chen, and Wang (2018) and Wang (2019) also supported the results because they found that the host country's economic growth is boosted by improved infrastructure. However, Yamin and Sinkovics (2009) found that MNE strategies harmed infrastructure development.…”
Section: 7mentioning
confidence: 81%
“…Literature on FDI and Infrastructure Nourzad, Greenwold, and Yang (2014) concluded that economic growth and infrastructure attract FDI. The study explored the relationship between foreign direct investment and infrastructure construction and confirmed that FDI improves infrastructure development; Sui, Huang, and Huang (2017) and Huang, Liu, Cai, Hao, and Lei (2018) for China, Chakrabarti et al (2017) for India and Jiang, Chen, and Wang (2018) and Wang (2019) also supported the results because they found that the host country's economic growth is boosted by improved infrastructure. However, Yamin and Sinkovics (2009) found that MNE strategies harmed infrastructure development.…”
Section: 7mentioning
confidence: 81%
“…1. Infrastructure Criterion: MNEs engage in FDI will consider the infrastructure of host country, including power plants and electricity network (Sovacool, Gilbert, & Nugent, 2014), water supply (Sargentis et al, 2019), telecommunication facilities (Tang et al, 2022), railways and roads, air and sea ports (Kabiru, 2016;Vlahinić-Dizdarević & Biljan-August, 2005;Wadhwa & Reddy, 2011), sanitation (Wang, 2019;Lawhon et al, 2023), internet popularization (Briglauer et al, 2018;Pazienza & Vecchione, 2009;Wadhwa & Reddy, 2011) and their combination.…”
Section: Efficiency Seeking Groupmentioning
confidence: 99%
“…International trade is one of the important things, especially in the economy of every country, it is useful for the welfare of its people (Wang, 2019). In addition, international trade also has an important role because each country cannot fulfill its needs by relying on what is in the country.…”
Section: Introductionmentioning
confidence: 99%